Fetishisation of knowledge: a case of patriotic history in Zimbabwe - Madziyauswa, Tafirenyika (African Books Collective, 2021)
This volume interrogates and theorises various forms of fundamentalism and fetishism that impinge on Africa and the African people. The book valiantly rethinks and unpacks these forms of fundamentalisms and fetishisms, offering in the process critical vistas for students, scholars and activists on matters of decoloniality and transformation. By meticulously and painstakingly unpacking pertinent issues, the book provides unparalleled intellectual milestones and platforms for the oncoming revolution and quest for justice in the form of decoloniality and transformation. Drawing from several disciplinary domains such as Development Studies, Security Studies, Political Anthropology and Sociology, Economic Anthropology and Social studies, English Studies, History, Philosophy and Religious Studies, and drawing from scholars from across different universities in the Southern African region, the book provides multiple lenses from which to understand the complex goings on in a continent that can no longer afford to simply fold hands and watch while its citizens suffer multiple forms of coloniality, fetishisms and fundamentalisms.